Giant congenital melanocytic nevus of the back: a case report - Idarto, Areta (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundGiant congenital melanocytic nevus (GCMN) is a rare disease with an extremely low incidence, that is present from or develops at birth and typically affects the dermis but may also affect other skin layers. Its incidence is estimated at <1 in 20,000 newborns. Despite its rarity, this lesion is important because it may be associated with severe complications such as malignant melanoma. A thorough follow-up is crucial since the probability of malignancy can vary depending on the clinical course. As such, careful observation is necessary to support possible management plans. Case DescriptionIn this case report, we present a three-day-old newborn male with abrasions on a black patch on his back. He presented with fever, jaundice, and black patches on more than 50% of his trunk down to the sacral area. The black raised patches resembling nodules had wounds on the lower back near the gluteus. A histopathology examination of specimens taken from 3 nodules on the back revealed hypocellular tissues with lymphocytes, histiocytes, neutrophils, fat droplets, and mature fat cells interspersed with some erythrocytes. The lesion was, therefore, diagnosed as a giant congenital melanocytic nevus (GCMN). Parents were counseled regarding the possible future course and were asked to come for regular follow-ups. Conclusions In this instance, we document a rare occurrence of GCMN that warrants recognition and appropriate treatment. To accumulate evidence for improving disease prognosis and outcomes, children with congenital melanocytic nev